Increasing Students’ Interest in Learning Islamic Religious Education Using the Gallery Walk Method - Hardimansyah, Hardimansyah (Jurnal Dirosah Islamiyah, 2024)
Choosing interesting and varied learning methods is an urgent demand for teachers today, to deliver meaningful learning. Among these methods is the Gallery Walk method. This research aims to determine the influence of the Gallery Walk method on students' interest in learning about Islam. The method used in this research is a quantitative research method. Data collection was carried out using observation, questionnaires and documentation at the Tarbiyah Iqra Kapuas Hulu College of Science, Indonesia. Data analysis was carried out using correlational descriptive tests for quantitative data. Based on the results of data analysis, it was concluded that: 1) there was a significant influence using the Gallery Walk method on students at the Tarbiyah Iqra Kapuas Hulu Science College with material on Principles and Practices of Islamic Economics, resulting in an average score of 3.87. 2) The students' interest in learning at the Tarbiyah Iqra Kapuas Hulu College of Science after using the Gallery Walk method with material on Principles and Practices of Islamic Economics was included in the high category, producing an average score of 3.90. (3) There is a significant influence between the Gallery Walk method and class learning interest which shows a strong positive relationship and has a valid regression equation Y= 24.417 + 0.687.